Explicit Port-Hamiltonian Formulation of Bond Graphs with Dependent Storages. Issue 2 (2020) - Pfeifer, Martin; Caspart, Sven; Muller, Charles; Pfeiffer, Silja; Krebs, Stefan; Hohmann, Sören
Abstract: Explicit port-Hamiltonian systems (PHSs) are the starting point for many powerful controller and observer design methods. It is well-known that explicit PHSs can be formulated on the basis of bond graphs. Indeed, the port-Hamiltonian formulation of bond graphs without dependent storages has been well investigated. However, little effort has been made towards bond graphs with dependent storages. This is a problem as dependent storages frequently occur in models from many engineering fields. In this paper, we address the explicit port-Hamiltonian formulation of bond graphs with dependent storages. Our idea is to express the port-Hamiltonian dynamics and output as functions of only the system inputs and independent storages. The main result is a rigorous and constructive method to formulate bond graphs containing dependent storages as explicit PHSs. An acadamic example illustrates and verifies our method.